1986
DOI: 10.1161/01.cir.74.3.583
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thrombolysis with tissue-type plasminogen activator by pretreatment with heparin.

Abstract: The effect of pretreatment with heparin on lysis of arterial thrombi by tissue-type plasminogen activator (rt-PA) was studied in 19 dogs. Copper coil-induced carotid artery thrombi were weighed, inserted into the femoral arteries, and exposed to a 15 min infusion of rt-PA at 10 ,ug/kg/min either with (n = 6 thrombi) or without pretreatment with a 200 unit/kg bolus of heparin (n = 6 thrombi). The infusion of rt-PA without pretreatment reduced the thrombus weight by 27.6 + 7.4%, while infusion of rt-PA with pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Blood was collected at baseline (before treatment allocation) and 45 minutes, 3 hours (end of alteplase infusion), 12 Figure 1. Median FPA plasma levels (with their 10th to 90th percentiles) at baseline were 21 ng/ml (2-390 ng/ml) in placebo-allocated patients (n = 166) and 18 ng/ml (2-210 ng/ml) in heparin-allocated patients (n=168) (p=NS).…”
Section: Blood Sampling and Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was collected at baseline (before treatment allocation) and 45 minutes, 3 hours (end of alteplase infusion), 12 Figure 1. Median FPA plasma levels (with their 10th to 90th percentiles) at baseline were 21 ng/ml (2-390 ng/ml) in placebo-allocated patients (n = 166) and 18 ng/ml (2-210 ng/ml) in heparin-allocated patients (n=168) (p=NS).…”
Section: Blood Sampling and Handlingmentioning
confidence: 99%
“…In placebo-treated patients, no significant correlation between plasma FPA levels and coronary patency was observed. (1-110) 23 8 ( (1-60) 25 8 (1-140) 98 25 (5-350) 40 28 (2-300) 12 hr 114 4 (1-56) 26 11 (2-240) 94 …”
Section: Blood Sampling and Handlingmentioning
confidence: 99%
“…Clot lysis and recanalization of the occluded coronary artery induced in vivo by t-PA can be accelerated by adjunctive ther apy with antiplatelet agents such as aspirin or antithrombin agents such as heparin and hiru din (28,29). It has been reported that heparin enhances thrombolysis and maintains coronary artery-patency after the administration of t-PA (6,30). As the balance between fibrin deposi tion and lysis is a key factor for thrombosis, we administered heparin to prevent the forma tion of fibrin and its incorporation into the thrombus during thrombolysis by plasminogen activators.…”
Section: Discussionmentioning
confidence: 99%
“…The canine model with a copper coil-induced femoral artery thrombus that was developed by Bush et al (25) and Cercek et al (26) was modified and used to examine the efficacy of the thrombolytic agents. Mongrel dogs (body weight: 9-15 kg) were anesthetized with sodium pentobarbital and artificially ventilated.…”
Section: Induction Of Thrombusmentioning
confidence: 99%
“…The blood concentrations of rt-PA and E6010 were measured by ELISA with a polyclonal antibody specific for t-PA (26,27 …”
Section: Administration Of Rt-pa and E6010mentioning
confidence: 99%